Presence and Genetic Identity of Symbiodiniaceae in the Bioeroding Sponge Genera Cliona and Spheciospongia (Clionaidae) in the Spermonde Archipelago (SW Sulawesi), Indonesia - van der Windt, Niels; van der Ent, Esther; Ambo-Rappe, Rohani; de Voogd, Nicole J. (Frontiers in Ecology and Evolution, 2020)
Members of the family Symbiodiniaceae form symbiotic relationships with several metazoan groups on coral reefs, most notably scleractinian corals. However, despite their importance to the health of coral reefs, their relationship with other host organisms such as bio-eroding sponges (Clionaidae) is still relatively understudied. In this study we investigate the presence and identity of Symbiodiniaceae in Clionaidae species in Indonesia and evaluate findings related to the evolution and ecology of the host-symbiont relationship. Clionaidae were collected throughout the Spermonde Archipelago in Indonesia. Morphological and molecular techniques were used to identify the sponge host (28S ribosomal RNA) and their Symbiodiniaceae symbionts (ITS2). Seven Clionaidae species were found, of which four species contained Symbiodiniaceae. Cliona aff. orientalis, Cliona thomasi and Spheciospongia maeandrina were host to Cladocopium, while Spheciospongia digitata contained Durusdinium and Freudenthalidium. In the remaining species: Cliona sp., Cliona utricularis and Spheciospongia trincomaliensis no evidence of the presence of Symbiodiniaceae was found. Our results provide the first record of Symbiodiniaceae in the sponge genus Spheciospongia. Additionally, we provide the first findings of Freudenthalidium and first molecular evidence of Durusdinium in bio-eroding sponges. Our results indicate coevolution between Spheciospongia digitata, Spheciospongia maeandrina and their symbionts. We discuss that the diversity of Symbiodiniaceae within bio-eroding sponges is likely far greater than currently reported in literature. Considering the threat bio-eroding sponges can pose to the health of coral reefs, it is crucial to understand Symbiodiniaceae diversity within Clionaidae and their effect on the functioning of Clionaidae species. We propose that the identity of the symbiont species is mostly to be related to the host species, but we did observe a potential case of environmental adaptation related to environmental stressors.